Presentation of the Special Issue of the 13th Principia International Symposium: Philosophy of Language and Linguistics - Jerzy A. Brzozowski; Ivan F. da Cunha (Principia: An International Journal of Epistemology)
This editorial presents the special issue with papers derived from presentations at the 13th Principia International Symposium, held in 2023. A brief context of the symposium is given, as well as an abstract of the keynote talks. Finally, the editorial introduces the main theme of the 14th Principia International Symposium, to be held in 2025.